DIACHRONIC EVOLUTION OF THE AXIOLOGICAL LEXICON IN BRITISH ENGLISH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article traces the development of value-laden vocabulary in British English across five historical periods: the medieval chivalric and Christian ethos; Renaissance humanism and emerging statehood; Enlightenment liberalism and press freedom; Victorian moral propriety and euphemism; and twentieth- and twenty-first-century ideals of democracy, diversity, and identity. By reviewing secondary data from authoritative online and scholarly sources, it identifies key terms—such as honour, virtue, liberty, duty, tolerance, sovereignty, and intersectionality—and situates them within their socio-cultural contexts. The study demonstrates how shifts in collective values are mirrored in the lexicon and discusses implications for contrastive axiological analysis and intercultural language pedagogy.